Microelectronics micro and nano-electronics and photonics - Lal, Krishan 1941- (Daya Pub. House, 2009)
Papers presented at the 6th International Workshop on Microelectronics, held at Islāmābād during 9-13 April 2007, organized by Centre for Science & Technology of the Non-aligned and Other Developing Countries jointly with the Institute of Information Technology